Uji Kualitas Air Sumur Dengan Menggunakan Metode MPN (Most Probable Numbers) - Novita Sunarti, Riri (BIOILMI, 2015)
Water used for drinking is healthy water that must meet the requirements of Bacteriology, based Kepmenkes RI No: 907 / Menkes / SK / VII / 2002 concerning the terms and monitoring the quality of drinking water, where for the value of the Most Probable Number (MPN) is 0 / 100 ml water samples were analyzed. In the method of testing microbiological quality of drinking water is used as an indicator Coliform group. The purpose of this study was to detect the presence of Coliform bacteria in water samples tested wells. Samples were tested in the form of water wells located in the Village RT.V Padang Jati. Research Well Water Quality Test Method Using MPN (Most Probable Numbers) was conducted in March 2014. This study uses observation deskription is through direct observation to determine the possibility of Coliform bacteria and fecal Coli. Data based on observations or surveys taken directly to the location you made to sample, as well as the examination of samples directly in the laboratory to obtain primary data. Results or Coliform MPN index and fecal Coli were compared using the formula 555 Thomas MPN table. The results showed that all samples test positive for Coliform bacteria, so it is not fit for use as drinking water.